Childhood poisoning causes and prevention; eight years of our rural hospital experience from South India - Malar, Ilango; Dorthy, V.; Newtonraj, Ariarathinam (International Journal Of Community Medicine And Public Health, 2021)
Poisoning is a significant public health problem, globally as well as in India.1 Poisoning among adults are mostly suicidal whereas among children are accidental in nature.2 In India, childhood poisoning is usually under reported as there is no proper surveillance system is available India and only hospital based data are available.2,3 We report our experience from a remote rural hospital from South India after getting institute ethical committee clearance for dissemination of data (Ref no. RC 18/55). We extracted the data of under-five children poisoning cases from poisoning register maintained in the hospital for the period of past eight years from 1st January 2012 to 31st December 2019. Total of 21 childhood poisoning were reported among them 12 (57%) were male and 9 (43%) were female. Most common poisoning was due to kerosene (8(38%)) followed by laundry bleaching detergent locally known as ‘Ala’ 5 (23%), pesticide poison 2 (10%), eucalyptus oil poisoning 2 (10%) and others like ant killer poisoning tablets overdose were 4 (19%). In children, poisoning are accidental nature and the amount consumed may also be less as the child has tendency for aversion due to smell and taste whereas in suicidal (deliberate poisoning) the dose will be higher to cause permanent damage and death.2 But unlike other poisoning a peculiar finding on reported eucalyptus oil poisoning was, in both cases eucalyptus oil was given to the children to consume as a medicine to cure respiratory tract infection and both of them presented with seizure and unconsciousness. Eucalyptus oil is advice as a topical medicine in the indigenous system of medicine but not as a parenteral medicine.4 In a place like India where there are prevailing false cultural beliefs, there is a need to educate and guide the people on misuse of medicines without proper advice, especially among children. A higher dose of eucalyptus oil poisoning may even result in death.5,6 Another important observation was bleaching detergent poisoning which is not properly reported other major studies from India, but this poisoning is the second most commonest among under-five children.2,3 This poison is an oxidizer and a corrosive in nature and on accidental ingestion may result in minor to transient adverse event with no sequelae in majority of cases.7